Working upstream: A statewide analysis of individual and contextual risk factors for future juvenile justice involvement among youth receiving prevention services - Sheppard, Keller (Criminology & public policy, 2024)
Research Summary Juvenile justice agencies are increasing their emphasis on early intervention and prevention services as a growing body of research evinces their effectiveness and cost efficiency. The present study analyzed the relationship between individual risk factors, contextual risk factors, and future juvenile justice involvement for 30,328 Florida youth residing in 3309 census tracts served by prevention programs. A series of two-level logistic regressions indicated that several distinct criminological domains (e.g., aggression, relationships, family, substance use, and attitudes/behaviors) predict future juvenile justice system involvement. However, education-related risk factors are among the most consequential for all youth, especially older youth. Concerning community context, neighborhood disadvantage directly affects system involvement, but only for youth under 12. Policy Implications These findings indicate the importance of addressing highly consequential risk factors—especially educational deficits—of youth in early intervention and prevention programs while also recognizing the impact of their social environments. Agencies attempting to work upstream with prevention services may benefit from prioritizing educational services and allocating resources to highly disadvantaged communities for early intervention programming.